Effects of CRT on atrial and ventricular arrhythmias in patients with HF - Taleski, Jane; Pocesta, B; Janusevski, F; Risteski, D; Poposka, Lidija (Oxford University Press (OUP), 2023)
Abstract Funding Acknowledgements Type of funding sources: None. Introduction Cardiac resynchronization therapy (CRT) is an accepted treatment for patients with heart failure (HF). Cardiac arrhythmias present a significant and complex issue in this patient group. Evidence exploring the influence of CRT on cardiac arrhythmias rate variations is limited. Purpose Our research investigates the effectiveness of CRT in the treatment of existing and newly diagnosed atrial and ventricular arrhythmias, and impact of epicardial lead position on these arrhythmias rate variations, as well as on the CRT response. Methods This single-center, prospective, observational study included 75 consecutive patients admitted for CRT implantation over a 12-month period. All included patients had episodes of atrial and/or ventricular arrhythmias, diagnosed by 12-lead ECG or 24-hour Holter monitoring. Pre-procedural demographic characteristics were collected for all patients, including ECG records, NYHA functional class, echocardiographic assessment of left ventricular ejection function and questionnaire for quality-of-life. During device follow up atrial and ventricular arrhythmias appearance was monitored. Additional assessment of echocardiographic parameters, NYHA - functional class, quality of life and rate of major cardiovascular complications and rehospitalizations was performed. Results The mean age of the patients was 62.4 ± 10.3 years, with 74.6% male and 25.3% females. 72% had a non-ischemic HF etiology. Pre-procedural paroxysmal AF was present in 34.7%, persistent AF in 36%, PVCs in 32%, NSVT 16%, and VT in 18,7% patients. 55% of the included patients were responders to CRT. Our results showed decrease in rate of all ventricular arrhythmias, with significant reduction in the percentage of VT (p=0.003), regardless of CRT response. Significant reduction of PVCs and NSVT rate (p=0.012 & p=0.024) was found in the responder group of patients. Regarding AF, our results showed a decrease in the number of AF events in both patient groups, however this was most visible in the responder patients with paroxysmal AF (p=0.057). In CRT responders, left ventricular pacing lead was most commonly located in a lateral branch vein of the CS with middle and mid/lateral position. In terms of quality of life and general condition of the patients, we noticed a significant improvement in the NYHA - functional class (p <0.001), as well as in both parts of the quality-of-life assessment questionnaire (p=0.0135, p<0.001). Conclusion CRT is an effective treatment for atrial and ventricular arrhythmias in HF patients, especially in responders to this therapy. LV epicardial lead position proved to be very important influence in the process of LV reverse remodeling, which is in direct correlation of the CRT responders and its effectiveness in reducing the rate of cardiac arrhythmias.